An ecological study of obesity-related cancer incidence trends in Australia from 1983 to 2017 - Eleonora Feletto; Ankur Kohar; David Mizrahi; Paul Grogan; Julia Steinberg; Clare Hughes; Wendy L. Watson; Karen Canfell; Xue Qin Yu (Elsevier, 2022)
Summary: Background: Overweight and obesity is a growing public health issue as it contributes to the future burden of obesity-related diseases, including cancer, especially in high-income countries. In Australia, 4.3% of all cancers diagnosed in 2013 were attributable to overweight and obesity. Our aim was to examine Australian age-specific incidence trends over the last 35 years for obesity-related cancers based on expert review (colorectal, liver, gallbladder, pancreas, breast in postmenopausal women, uterine, ovary, kidney, thyroid, and multiple myeloma) individually and pooled. Methods: Australian incidence data for 10 obesity-related cancers among people aged 25-84 years, diagnosed from 1983 to 2017, were obtained from the Australian Cancer Database. We used age-period-cohort modelling and joinpoint analysis to assess trends, estimating incidence rate ratios (IRR) by birth-cohort for each individual cancer and pooled, and the annual percentage change. The analyses were also conducted for non-obesity-related cancers over the same period. Findings: The total number of cancers where some proportion is obesity-related, diagnosed from 1983-2017, was 1,005,933. This grouping was 34.7% of cancers diagnosed. The IRR of obesity-related cancers increased from 0.77 (95% CI 0.73, 0.81) for the 1903 birth-cohort to 2.95 (95% CI 2.58, 3.38) for the recent 1988 cohort relative to the 1943 cohort. The IRRs of non-obesity related cancers were stable with non-significant decreases in younger cohorts. These trends were broadly similar across sex and age groups. Interpretation: The incidence of obesity-related cancers in Australia has increased by birth-cohort across all age-groups, which should be monitored. Obesity, a public health epidemic, needs to be addressed through increased awareness, policy support and evidence-based interventions. Funding: This research received no specific funding.